Increasing the Economic Value of Cow Manure Into Vermicompost - Khaliqi, Muhammad; Gurning, Herfita Rizki Hasanah; Simatupang, Dewi Ratna Sari; Yola Anggi,; S. Pelawi, Rizky Aulia Nazlita; Dedy Darmansyah, (Journal of Saintech Transfer, 2022)
The average farmer in Kota Datar Village has a livelihood as a breeder, especially cattle farming. Maintenance is carried out by keeping in the cage all the time, so that animal waste is only left to accumulate around the cage. Moreover, during the rainy season, livestock manure cannot be processed into compost, the resulting pollution has the potential to widen into the realm of social problems. The limited use of livestock manure as compost and its low selling value makes farmers feel unwilling to use it. With the cultivation of earthworms, this manure can produce vermicompost. In addition to the content of nutrients and growth hormones contained in vermicompost, the selling value of the fertilizer is also higher when compared to other compost fertilizers. The method of implementing this service was by conducting socialization and training as well as the practice of making vermicompost.